Five Minute Screencasts - The Super Tool for Science and Engineering Librarians. - Olivia Bautista Sparks (Issues in Science and Technology Librarianship, 2010)
Online tutorials provide an alternative to in-person or in-class library instruction and can be indispensable for reaching large student bodies, especially when combined with existing web-based guides, i.e. LibGuides, and course management resources, i.e. Blackboard. Unfortunately, professional-looking tutorials take time, money and expertise to develop; these are commodities that our underfunded and understaffed libraries may not have available. Recently developed screencasting services make online tutorial creation both free and easily done by science and engineering librarians. [ABSTRACT FROM AUTHOR]